Associations of modern initial antiretroviral drug regimens with all-cause mortality in adults with HIV in Europe and North America: a cohort study. Issue 6 (June 2022) - Trickey, Adam; Zhang, Lei; Gill, M John; Bonnet, Fabrice; Burkholder, Greer; Castagna, Antonella; Cavassini, Matthias; Cichon, Piotr; Crane, Heidi; Domingo, Pere; Grabar, Sophie; Guest, Jodie; et al.
Summary: Background: Over the past decade, antiretroviral therapy (ART) regimens that include integrase strand inhibitors (INSTIs) have become the most commonly used for people with HIV starting ART. Although trials and observational studies have compared virological failure on INSTI-based with other regimens, few data are available on mortality in people with HIV treated with INSTIs in routine care. Therefore, we compared all-cause mortality between different INSTI-based and non-INSTI-based regimens in adults with HIV starting ART from 2013 to 2018. Methods: This cohort study used data on people with HIV in Europe and North America from the Antiretroviral Therapy Cohort Collaboration (ART-CC) and UK Collaborative HIV Cohort (UK CHIC). We studied the most common third antiretroviral drugs (additional to nucleoside reverse transcriptase inhibitor) used from 2013 to 2018: rilpivirine, darunavir, raltegravir, elvitegravir, dolutegravir, efavirenz, and others. Adjusted hazard ratios (aHRs; adjusted for clinical and demographic characteristics, comorbid conditions, and other drugs in the regimen) for mortality were estimated using Cox models stratified by ART start year and cohort, with multiple imputation of missing data. Findings: 62 500 ART-naive people with HIV starting ART (12 422 [19·9%] women; median age 38 [IQR 30–48]) were included in the study. 1243 (2·0%) died during 188 952 person-years of follow-up (median 3·0 years [IQR 1·6–4·4]). There was little evidence that mortality rates differed between regimens with dolutegravir, elvitegravir, rilpivirine, darunavir, or efavirenz as the third drug. However, mortality was higher for raltegravir compared with dolutegravir (aHR 1·49, 95% CI 1·15–1·94), elvitegravir (1·86, 1·43–2·42), rilpivirine (1·99, 1·49–2·66), darunavir (1·62, 1·33–1·98), and efavirenz (2·12, 1·60–2·81) regimens. Results were similar for analyses making different assumptions about missing data and consistent across the time periods 2013–15 and 2016–18. Rates of virological suppression were higher for dolutegravir than other third drugs. Interpretation: This large study of patients starting ART since the introduction of INSTIs found little evidence that mortality rates differed between most first-line ART regimens; however, raltegravir-based regimens were associated with higher mortality. Although unmeasured confounding cannot be excluded as an explanation for our findings, virological benefits of first-line INSTIs-based ART might not translate to differences in mortality. Funding: US National Institute on Alcohol Abuse and Alcoholism and UK Medical Research Council.